The Spillover Effects from Foreign Direct Investment (FDI) on Labor Productivity: Evidence from Indonesian Manufacturing Sector [Efek Spillover dari Foreign Direct Investment (FDI) terhadap Produktivitas Tenaga Kerja: Studi pada Sektor Manufaktur Indonesia] - Riesta Karentina (Pusat Penelitian, Badan Keahlian DPR RI, 2019)
Despite growing concern regarding the productivity benefits of foreign direct investment (FDI), few studies have been conducted on the impact of FDI spillovers on domestic firms’ labor productivity in Indonesia. This study aims to do three things. First, it examines the effect of FDI spillovers on domestic firms’ productivity. Second, it investigates the short-term and long-term effects of FDI spillovers on domestic firms’ productivity. Third, it explores the impact of FDI spillovers on domestic firms’ productivity in different groups of industries based on their factor intensity. Micro-level panel data covering about 20,000 medium and large manufacturing establishments in each year over the period 2010 and 2014 was employed. This study suggests that, within the same industry, horizontal spillovers are associated with domestic firms’ productivity: this relationship is negative in the short-term but positive in the long-term. This study’s findings also demonstrate that, across industries, there are negative backward spillover effects on domestic firms’ productivity. In addition, this study points out that FDI spillovers affect domestic firms’ productivity effectively when they are capital-intensive. Therefore, the results imply the importance of maintaining a long-term perspective toward foreign-invested firms in Indonesia and the government needs to stimulate policies that can enhance domestic firms’ capacity to supply intermediate materials and capital to foreign firm in downstream market by truncating the technology gap between foreign and domestic firms.Keywords: FDI spillovers, horizontal spillover, backward spillover, labor productivityAbstrakMeskipun perhatian terkait manfaat foreign direct investment (FDI) terhadap produktivitas semakin berkembang, masih sedikit penelitian yang menguji pengaruh FDI spillovers terhadap produktivitas tenaga kerja pada perusahaan domestik di Indonesia. Penelitian ini bertujuan untuk melakukan tiga hal. Pertama, menguji pengaruh FDI spillovers terhadap produktivitas perusahaan domestik. Kedua, menginvestigasi dampak jangka pendek dan jangka panjang dari FDI spillovers terhadap produktivitas perusahaan domestik. Ketiga, menelaah lebih dalam dampak dari FDI spillovers terhadap produktivitas perusahaan domestik pada kelompok industri yang berbeda berdasarkan intensitas faktor produksinya. Penelitian ini menggunakan mikro panel data yang mencakup kurang lebih 20.000 perusahaan industri manufaktur sedang dan besar tiap tahunnya pada tahun 2010-2014. Hasil estimasi menunjukkan bahwa, di industri yang sama, horizontal spillovers memiliki pengaruh negatif terhadap produktivitas perusahaan domestik di jangka pendek namun positif pada jangka panjang. Hasil estimasi juga menunjukkan bahwa di industri yang berbeda, backward spillovers berdampak negatif terhadap produktivitas perusahaan domestik. Selain itu, FDI Spillovers memengaruhi produktivitas perusahaan domestik dengan lebih efektif ketika industri tersebut capital-intensive. Dengan demikian, hasil penelitian menunjukkan pentingnya mempertahankan perspektif jangka panjang terhadap perusahaan investasi asing di Indonesia, dan pemerintah perlu untuk menstimulasi kebijakan yang dapat meningkatkan kapasitas perusahaan domestik dalam memasok barang setengah jadi dan barang modal ke perusahaan asing di pasar hilir dengan cara memotong kesenjangan teknologi antara perusahaan asing dan domestik.Kata kunci: FDI spillovers, horizontal spillover, backward spillover, produktivitas tenaga kerja